Diaspora and postmodern fecundity - Bishnupriya Ghosh; Bhaskar Sarkar (Communicare)
Central to the experience of postmodernity is the increase in, and the intensification of, transnational encounters. The globalization of capital, culture, work-forces, and identities leads to patterns of homogenization whose totalizing tendency is undercut by intense fragmentation and the local play of differences. The increased productivity in economic and cultural terms marks the postmodern as remarkably fecund. This perception of fecundity comes from the various, and often opposing, groups on the political continuum.1 The 'triumph' of transnational capital in Asia and the entry of Eastern Europe into the capitalist fold have created unprecedented economic and financial flows. Simultaneously, the antifoundational dismantling of epistemological hierarchies release long-repressed energies that create new flows and open up fresh possibilities. These new flows and structuration’s require cognitive refrigeration, as older modes of knowing the world have become inadequate. The nation is one social and cultural formation that has come to be rigorously Interrogated in the light of the global-local· dynamisms. A rise in the volume of migrations and the increasing visibility of varied diasporas - communities that transcend the geopolitical boundaries of the nation-state - demand a new sense of national belonging: national heritage, essence, tradition etc. have lost their immanent valences. For instance, Chow (1993) stresses the need to "unlearn Chinese ness" in order to foster Chinese diasporic identity.